2019
DOI: 10.31294/w.v11i2.6213
|View full text |Cite
|
Sign up to set email alerts
|

An Error Analysis of English Plosive and Fricative Consonants at Vocational High Schools

Abstract: The purpose of the research is to analyze plosive and fricative consonants pronunciation errors in recordings that made by students in vocational high school in Jakarta. The research method that used to analyze plosive and fricative consonants pronunciation errors in recordings that made by the students is descriptive qualitative method and based only on a few sound recordings. After the researcher analyzes the recordings, the researcher then found that the students still make the errors in pronouncing the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…As a result, we already have our first answer as to why the majority of students struggle to pronounce the voiceless dental fricative, which is that they are unable to produce a breath of air from the air passage in the vocal chords when they place their tongue behind the incisors (Wafi et al, 2020), and this occurrence is typical of people who are pronouncing the voiceless dental fricative (Fauzi, 2020). When the point of articulation to pronounce the dental fricative consonant /θ/ is incorrect, the consonant /θ/ is also put as the consonant /f/ in by the students (Putra, 2019). This occurrence is also seen in Slovakian students (Metruk, 2017), and it appears that in this study, the percentage of students who chose consonant /f/ as a replacement for / θ/ is greater since both are in the form of a minimum pair.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we already have our first answer as to why the majority of students struggle to pronounce the voiceless dental fricative, which is that they are unable to produce a breath of air from the air passage in the vocal chords when they place their tongue behind the incisors (Wafi et al, 2020), and this occurrence is typical of people who are pronouncing the voiceless dental fricative (Fauzi, 2020). When the point of articulation to pronounce the dental fricative consonant /θ/ is incorrect, the consonant /θ/ is also put as the consonant /f/ in by the students (Putra, 2019). This occurrence is also seen in Slovakian students (Metruk, 2017), and it appears that in this study, the percentage of students who chose consonant /f/ as a replacement for / θ/ is greater since both are in the form of a minimum pair.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies by Adhani et al (2021), Situmeang &Lubis (2020), andEldika &Zainil (2022) examined the significant challenges students faced in pronouncing English fricatives, attributing the difficulties to factors such as a lack of knowledge of the proper pronunciation of consonant fricatives. A study conducted by Putra (2019) also explores the examination of students' pronunciation issues in plosive and fricative consonants. The primary source of errors was determined to be students lack of comprehension on proper pronunciation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, until they are adults, they continue to speak in the same manner. This habit becomes the reason for English pronunciation errors because it is difficult for them to reset the speech organ to produce the speech sound of this language (Putra, 2019;Ramelan, 2003). In other words, Indonesian-speaking learners will develop the phonemes of Indonesian which are difficult for them to change their movements of speech organs since it has been deeply implanted in them as part of their habits.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Putra (2019) did research to examine pronunciation faults of plosive and fricative consonants in recordings generated by students at a Jakarta vocational high school. His research employed the qualitative method, and the results showed that 64% of pupils and 36% of plosives respectively produced consonant errors.…”
Section: Introductionmentioning
confidence: 99%